Frontiers in Optics + Laser Science 2021 2021
DOI: 10.1364/fio.2021.jth5a.122
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Phase Noise at Comb-Line Frequencies in a Frequency Comb

Abstract: We calculate the phase noise in a modified uni-traveling carrier photodetector for frequency comb applications. In contrast to a continuous wave, a frequency comb is characterized by a distinct phase noise for each comb line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Li et al [2] designed and studied an MUTC photodetector that was later analyzed by Mahabadi et al [3]. Recently we have extended the work of [3] by calculating the phase noise at the first 100 comb-line frequencies in this detector [4]. We found that the phase noise increases non-monotonically as a function of comb-line frequencies.…”
Section: Introductionmentioning
confidence: 76%
“…Li et al [2] designed and studied an MUTC photodetector that was later analyzed by Mahabadi et al [3]. Recently we have extended the work of [3] by calculating the phase noise at the first 100 comb-line frequencies in this detector [4]. We found that the phase noise increases non-monotonically as a function of comb-line frequencies.…”
Section: Introductionmentioning
confidence: 76%